GEOCHEMICAL AND PETROLOGICAL CHARACTERISTICS OF DEH SIAHAN GRANITIC ROCKS, SOUTHWEST OF KERMAN, IRAN: DATA BEARING ON GENESIS (Journal of Sciences, Islamic Republic of Iran)
The Oligocene-Miocene granitic rocks of Deh Siahan, part of central Iranian volcanic belt, are intruded into Eocene volcano-sedimentary complex where their contact is marked by albite-epidote hornblende hornfels facies and granitic apophyses. The granitic rocks show enhanced LIL element abundances and low HFS/LIL ratios. Geochemical data, various trace element discriminant diagrams, enhanced Y/Nb and Ce/Nb ratio, and ocean ridge granite normalized multi-element diagrams indicate that the Deh Siahan granitic rocks have characteristics of high-K, calc-alkaline, I-Cordilleran type granites of volcanic arc settings. In this aspect, it may represent part of an Andean-type magmatic arc formed in response to subduction of Neotethys oceanic crust beneath Central Iran, unrelated to a rift settings. The partial melting of subducted oceanic crust led to the formation of basic magma. Its emplacement under the mantle wedge provoked melting in the considerably metasomatized and enriched sub-continental lithosphere. This caused generation of siliceous magma which its low pressure crystal fractionation eventually led to the formation of Deh Siahan granitic rocks.